Characterization of spark plasma sintered TiC–Si3N4 ceramics. (February 2021) - Pazhouhanfar, Yaghoub; Delbari, Seyed Ali; Shahedi Asl, Mehdi; Shaddel, Shahrzad; Pazhouhanfar, Morteza; Le, Quyet Van; Shokouhimehr, Mohammadreza; Mohammadi, Mohsen; Sabahi Namini, Abbas
Abstract: This research aimed to compare the TiC and TiC-Si3 N4 ceramics in terms of sintering behavior and physical-mechanical characteristics. The spark plasma sintering (SPS) process was used as the fabrication route with the sintering conditions of 1900 °C, 7 min, and 40 MPa. The results confirmed the deposition of carbon in the monolithic TiC during the SPS process. Incorporating Si3 N4 led to the advancements of some chemical reactions between TiC, Si3 N4, and carbon ingredients, leading to the in-situ formation of SiC and N2 phases. Although the thermodynamic assessment suggested the in-situ synthesis of the TiN phase, too, any amount of it was identified in neither the X-ray diffractometry pattern nor field emission scanning electron microscopy images. Based on the thermodynamic study, TiN possibly reacted with the deposited carbon, forming in-situ TiC and N2 . Thermal conductivity, Vickers hardness, and flexural strength of 10.1 W/mK, 2966 HV0.1kg, and 219 MPa, respectively, were obtained for the TiC-Si3 N4 ceramic. Highlights: Sintering, microstructure and characteristics of TiC-Si3 N4 ceramics were studied. Incorporating Si3 N4 in TiC led to the in-situ formation of SiC and N2 phases. Thermal conductivity and mechanical properties were measured and compared.